Playce - Haddox, Elizabeth (Kansas State University, 2015)
Urban play is a type of play: it is an emotionally engaging act where players take part in fun within definable spatial parameters (Huizinga, 1944; Caillois, 1961). Urban play is unusual, though, because it occurs at the human scale, and uses the city fabric as the setting. As atypical reappropriations of space, urban play activities like parkour, flash mobs, and geocaching layer diverse experiences at specific city sites. This layering may ultimately develop place phenomena such as insideness. It is also possible that pre-existing concepts of place may influence where people choose to play. The subject of this investigation was to understand the relationship between urban play and place for players. Understanding this relationship can inform landscape architects and urban designers about urban play and how to design for playability. I used informed grounded theory (Thornberg, 2012) and autoethnography (Ellis, Adams, & Bochner, 2012) to structure a mixed-methods study of urban play and place. I myself engaged in play and wrote field notes to gather data and inform my other data collection and analysis. I played with many other players, and conducted on-site, walk-along interviews with six of them. Recordings of the verbal exchanges, maps of the paths of the interviews, and photographs of landscape conditions identified as salient to play or place were collected during the interviews. This variety of data was understood through several memoing strategies, including note-taking, mapping, and sketching. Memoing and reflective “memoing-on-memos” abstracted the data enough for me to construct overarching themes, or findings (Thornberg, 2012; Glaser & Strauss, 1967; Strauss & Corbin, 1990). Data collection and analysis were situated within an extensive literature review. Four primary findings resulted from my investigation. First, that the physical landscape influences play. Second, that play influences the social landscape. Third, that play develops sense of neighborhood. And fourth, that play relates to the physical and social landscapes at multiple scales. My findings can help designers understand what playability is and design for urban play.
Keywords: Urban play; Place; Grounded theory; Autoethnography; Playability; Landscape Architecture (0390)